Clinical implications of the hepatomesenteric trunk–case report and literature review - Mark Shacker; Artur Rybachok; Benjamin R. Paul; Manuel Cevallos (Translational Research in Anatomy)
Purpose: Variants of the abdominal vasculature profoundly impact the fields of interventional radiology and surgery. The “hepatomesenteric trunk” is a unique abdominal variant wherein the common hepatic artery arises directly from the superior mesenteric artery. Methods: A narrative literature review was conducted to thoroughly characterize the hepatomesenteric trunk, including its reported prevalence, embryological origin, and implications in clinical practice. A detailed description of this variant found in a donor was also presented. Results: The prevalence of the hepatomesenteric trunk ranges from 1.0 to 4.5 % in ten comprehensive studies. In as many as 90 % of cases, the hepatomesenteric trunk may be accompanied by a “gastrosplenic trunk,” wherein the left gastric and splenic arteries share a common origin. Significance: This variant uniquely impacts foregut and midgut perfusion, and knowledge of this and other splanchnic arterial variants is essential for procedures such as pancreaticoduodenectomy, arterial reconstruction, mesenteric revascularization, and transarterial chemoembolization. A detailed preoperative workup, meticulously planned surgical approach, and comprehensive knowledge of such variants are essential to mitigate the risk of vascular injury in abdominal procedures.